PERAN PROMOSI MEDIA SOSIAL PADA PEMILIHAN PROGRAM STUDI MANAJEMEN BISNIS SYARIAH - Yulfan Arif Nurohman; Alvin Yahya; Rina Sari Qurniawati (Among Makarti, STIE AMA Salatiga, 2019)
AbstractFor two consecutive years the Islamic Business Management Study Program (MBS) of IAIN Surakarta received an award from SPAN-UM PTKIN (National Academic Achievement Selection - State Islamic Religious College Entrance Examination) in the highest number of applicants in the State Islamic Institute (IAIN) category. The selection of the right study program is a hope for prospective students as a provision for the future. Various sources of information are sought to obtain information related to study programs. The development of information technology makes social media a tool used in marketing. Respondents in this study were 101 Islamic Business Management Study Program students. Data collection techniques using survey methods by giving questionnaires to respondents. In testing the research model, researchers used descriptive analysis methods and linear regression on the SPSS statistical program to test the validity, reliability and research hypothesis. The results of the study show that there is a relationship between the role of social media promotion in the selection of study programs. This is shown in the variables of personal relevance, message and brand familiarity, there is a positive influence on the selection of study programs. So, it can be said that the official social media accounts owned by IAIN Surakarta Syariah Business Management Study Program (MBS) can build trust in their followers to keep up with the latest information through social media so as to increase value. Keywords : media sosial, personal relevance, interactivity, message, brand familiarity